Digital controller design of an industrial sewing station using evolutionary algorithms - Moretti, Eric Henrique (2020)
Development of increasingly efficient production methods is a competiveness driving factor for any company. Today, many of these improvements include the integration of technology-based solutions into processes traditionally operated by humans. In this context, the present work aims to report the controller performance of a prototype developed for semi-automatic sewing stations. This project was fostered by “Factory Play”, a Portuguese company that produces inflatable structures, under the technical supervision of the Polytechnic Institute of Bragança. At the present time, the sewing station travel speed is regulated by an embedded PID controller that has been previously tuned using classical methods. However, even if the overall performance is currently acceptable, additional experiments were made regarding the use of evolutionary based algorithms to attain a better dynamic response and flexibility. This article present the results obtained using those methods where it is possible to confirm that the use of evolutionary algorithm will simplify the design process while consistently leading to a suitable solution.